EXPEDIENTE - v17n3 - Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Mendes, Deise Maria Leal Fernandes; Valentim, Renata Patrícia Forain de (Estudos e Pesquisas em Psicologia, 2018)
EXPEDIENTE - v17n3